2016
DOI: 10.4149/neo_2016_604
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling analysis of the role of miR-22 in clear cell ovarian cancer

Abstract: This study aimed to investigate the role and potential mechanism of miR-22 in clear cell ovarian cancer (CCOC) progression. The gene expression profile of GSE16568, including 3 CCOC samples with miR-22 overexpression and 3 negative controls, was downloaded from the Gene Expression Omnibus database. Differentially expressed genes (DEGs) were screened using the limma package in R. Gene Ontology (GO) and pathway enrichment analysis of DEGs were performed by using The Database for Annotation, Visualization and Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…20) For instance, the lower miR-22 expressions are found in hundreds of clinical samples of the osteosarcoma, rhabdomyosarcoma, prostate, cervical and lung primary tumors. 8,12) miR-22 expression detected by RT-qPCR is significantly downexpressed in the osteosarcoma MG-63 cells 21) and tissues. 11) The expression of miR-22 in hepatocellular carcinoma (HCC) tissues and cell lines are much lower than that in normal control.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…20) For instance, the lower miR-22 expressions are found in hundreds of clinical samples of the osteosarcoma, rhabdomyosarcoma, prostate, cervical and lung primary tumors. 8,12) miR-22 expression detected by RT-qPCR is significantly downexpressed in the osteosarcoma MG-63 cells 21) and tissues. 11) The expression of miR-22 in hepatocellular carcinoma (HCC) tissues and cell lines are much lower than that in normal control.…”
Section: Discussionmentioning
confidence: 98%
“…11) Furthermore, miR-22 contributes to cellular differentiation, migration and invasion by regulating its downstream transcription factors. 12,13) Notch pathway is an evolutionarily conserved signaling pathway which is activated to release the intracellular domain of Notch (NICD) to activate the Notch target genes Hes-1 and c-Myc. The Notch family consists of four receptors and five ligands.…”
mentioning
confidence: 99%
“…In our study, we identified ten pathways significantly enriched with the miR-22 anticorrelated genes related to cell cycle, CDK6 and CDKN1A . CDK6 is a member of the CDK family, which comprises heteromeric serine/threonine kinases that control progression and regulate mammalian cell division through the cell cycle in collaboration with their regulatory subunits, the cyclins [ 61 , 62 ]. CDKN1A is a CDK inhibitor which physically interacts with, and inhibits, the activity of cyclin-CDK2, -CDK1, and -CDK4/6 complexes, preventing phosphorylation of critical cyclin-dependent kinase substrates thus functioning as a regulator of cell cycle progression during the G1 and S phases [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…CDKN1A is a CDK inhibitor which physically interacts with, and inhibits, the activity of cyclin-CDK2, -CDK1, and -CDK4/6 complexes, preventing phosphorylation of critical cyclin-dependent kinase substrates thus functioning as a regulator of cell cycle progression during the G1 and S phases [ 63 ]. Interestingly, both CDK6 and CDKN1A are involved in p53 signaling pathway, suggesting that the p53–miR-22– CDK6 and/or CDKN1A axis could play a major regulatory role in the determination of p53-dependent apoptosis [ 61 , 64 , 65 ]. In particular, CDKN1A regulation by miR-22 has been shown to selectively determine the induction of p53-dependent apoptosis over cell cycle arrest acting as a molecular switch for the determination of p53-dependent cellular fate in response to various oncogenic stresses characterized by different damage intensity [ 65 ].…”
Section: Discussionmentioning
confidence: 99%